Aspectos epidemiológicos no câncer colorretal em pacientes jovens atendidos no HUJBB no período de jan. 1996 a dez. de 2006 - QUEIROZ, Alzira Gomes de (2023)
OBJETIVE: Analyze the epidemiologic aspects of young patients (age inferior to 40) with colorectal cancer. METHODOLOGY: 23 young patients (under 40) were studied retrospectively, average age 28 years old, and operated at HUJBB, due to colorectal cancer. The existences of colorectal cancer risk factors, clinical aspects, and anatomic pathological characteristics were evaluated to identify the kind of surgical treatment. RESULTS: No difference between both sexes was found. The average time between the first symptoms and the diagnosis was of ten months. The most prevalent signs and symptoms were the alteration of the intestinal habit. Most of the patients deny a positive family history of colorectal cancer. As for the location of the primary tumor, 39,13% were located in the rectum, 17,39% in the sigmoid, 21,74%in the rectum sigmoid, on the left colon 8,70% of the cases, no case on the transverse colon, 13,04% of the cases on the right colon. Carcinomatosys peritoneal was present 34,78%. In most of the cases (56,25%), the surgery was done in curative nature, prevailing the amputation of the abdomen perineal of the rectum. Less differentiated adenocarcinoma presented higher indicators of CEA before surgery. CONCLUSION: Patients with colorectal cancer, under 40 years old, are usually symptomatic and the disease is advanced prior the diagnosis.